SAT0349 Assessment of Postural Stability in Patients with Knee Osteoarthritis: A Pilot Study. (23rd January 2014) - Perez-Guijo, V.; Garrido-Castro, J. L.; Collantes-Estevez, E.; Gonzalez-Navas, C.; Gil-Cabezas, J.; Garcia-Rodriguez, M. A.; Font-Ugalde, P.
Abstract : Background: Knee osteoarthritis (OA) is the most common disease affecting human locomotion, and one of the most important causes of disability among the elderly population. In order to assess health status of patients self-evaluated questionnaires are commonly used, wich may be influenced by certain degree of subjectivity. Hialuronic acid is a common used treatment to improve knee OA. A force plate connected to a computer allows to analyze postural stability evaluating the center of pressure (CoP) sway in the lateral and sagittal planes. These methods of assessment the postural stability have shown excellent reliability in previous studies. Objectives: Analyze the assessment of postural stability in patients with Knee OA using a triaxial force plate. Methods: 10 patients with knee OA were analyzed (6 women and 4 men, age 55.3±3.2 years, weight 82.5±12.9 Kgr.) and 6 healthy subjects (4 women and 6 men, age 53.1±1.6 years, weight 78.3±10.4 Kgr.) as control group. Patients had a II-II degree of knee OA according to Kellgren and Lawrence scale. Hyaluronic acid injections were applied into the affected knee. Measures were taken before and after (4 weeks) treatment. A triaxial force plate (Bertec © FP5040) was used to assess postural balance. Patiens remained quiet for 10 seconds on the force plate, first with their eyes open (EO) and then another 10 seconds with their eyes closed (EC). Following parameters were recorded: total CoP distance, distance covered in antero-posterior and medio-lateral directions, area covered, and Romberg test (relation between EC and EO area). Patients fulfilled questionnaires in each test in order to calculate indexes: VAS general, VAS pain, WOMAC, SF-36 and OARSI criteria. Results: Significant differences were observed in CoP area in both EO and EC, and in Romberg test, between pre and post treatment measures. Differences between control group and patients were significant in almost all parameters. In questionnaires based indexes, improvements were showed, although these differences were not statistically significant. Correlations were found between CoP sway with EC (p<0.05) and Romberg test (p<0.05) with pain according to VAS. SF-36 index also correlated (p<0.05) with CoP sway in both EO and EC. Conclusions: Despite being a pilot study, with a very reduced sample, measurements of postural stability obtained from the force plate were sensitive to treatment. It was also interesting correlations between balance and pain level according to VAS, wich seems to show that pain in knee OA produces certain postural imbalance, as previous studies shown. Future studies with larger sample size may demonstrate our hypothesis, so this kind of technology can be used to assess outcome in knee OA patients and to show effectiveness treatments. Disclosure of Interest: None Declared